Enhancing farmer engagement on the targets and indicators of the Global Goal on Adaptation (GGA) - Cramer, Laura (2025)
The Eastern Africa Farmers Federation (EAFF) collaborated with Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) to host a workshop aimed at ensuring farmers' voices are central to shaping the Global Goal on Adaptation (GGA). The workshop brought together farmers, negotiators, researchers, and climate experts to review and advocate for these indicators, emphasising local perspectives in global climate resilience frameworks. This presentation was used to open the workshop, it provides the workshop objectives and expected outcomes as well as the workshop programme.